Neurofibromatosis type 2: A challenging case report and multidisciplinary management approach - Muhammad Usman,; Syed Muhammad Salman Hassan,; Maria Batool,; Ramisha Chaudhary,; Salman Ahmed Malik, (Journal of the Pakistan Medical Association, 2025)
Neurofibromatosis type 2 (NF2) is a genetic disorder characterised by multiple benign tumours in the nervous system. We present the case of a 16-year-old female with NF2, seen on April 29, 2023, at Nishtar Hospital, Multan, exhibiting symptoms such as swollen left eye, chronic headache, decreased vision, bilateral hearing loss, tinnitus, and gait issues. Diagnostic evaluation, including Magnetic Resonance Imaging (MRI), confirmed NF2 diagnosis based on National Institutes of Health (NIH) and Manchester criteria. Surgical resection is the primary treatment, but the patient refused and opted for herbal treatment due to personal and socioeconomic reasons. The report highlights the challenges in NF2 management and the importance of patient preferences. Keywords: Neurofibromatosis; Neurological Disorders; Radiology.